Novel transcripts of EMT driving the malignant transformation of oral submucous fibrosis - Smitha Sammith Shetty; Kanaka Sai Ram Padam; Mohit Sharma; Adarsh Kudva; Pratik Patel; Raghu Radhakrishnan (Scientific Reports, 2025)
Abstract Oral submucous fibrosis (OSF) is a chronic, progressive, and fibrotic condition of the oral mucosa that carries an elevated risk of malignant transformation. We aimed to identify and validate novel genes associated with the regulation of epithelial-to-mesenchymal transition (EMT) in OSF. Genes regulating EMT were identified through differential gene expression analysis, using a LogFC threshold of -1 and + 1 and a padj value < 0.05, based on data from GEO datasets and the TCGA-HNSC datasets. The curated EMT genes were correlated with functional cancer states and subjected to clustering to identify candidate genes. Integration of bioinformatics and proteomics led to the discovery of the EMT genes MMP9, SPARC, and ITGA5 as novel candidates. Comprehensive pathway and immunohistochemical analyses confirmed their roles in regulating EMT in OSF, oral squamous cell carcinoma (OSCC), and OSF-associated squamous cell carcinoma (OSFSCC). The significant roles of MMP9, SPARC, and ITGA5 in fibrosis and malignancy suggest a novel mechanism in which fibrosis-associated type 2 EMT undergoes transition to type 3 EMT, driving OSF towards malignancy.